Analisis Pembelajaran dan Penyelesaian Soal Matematika Menggunakan Software Maple Calculator Pada Siswa Berbasis Android - Titin Anisa Tanjung; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Mathematics is a discipline characterized by its abstract nature and reliance on logical reasoning. Therefore, it is essential to choose a teaching method that facilitates students' comprehension of the subject matter and fosters their logical thinking abilities. The software is a suitable form of media for the latest advancements in technology. Presently, technology is advancing at a rapid pace and is not only utilized in daily life but can also be employed in the process of learning mathematics. Software facilitates students' comprehension of lessons by enabling them to effortlessly solve questions. Furthermore, the Maple Calculator program is a straightforward and practical tool. The Maple calculator software offers a range of tools to assist students in solving mathematical problems, including integrals and trigonometry. It provides numerous features and functionalities. It has the potential to assist students in resolving their difficulties and is anticipated to enhance students' motivation for studying mathematics. The objective of this publication is to examine the proper and accurate utilization of the Maple Calculator program.